Role of irisin in physiology and pathology - Liu, Shiqiang; Cui, Fengqi; Ning, Kaiting; Wang, Zhen; Fu, Pengyu; Wang, Dongen; Xu, Huiyun (Frontiers in Endocrinology, 2022)
Irisin, out-membrane part of fibronectin type III domain containing 5 protein (FNDC5) was activated by PPARγ coactivator-1α (PGC-1α) during physical exercise in skeletal muscle tissues. Most studies have reported that the concentration of irisin is highly associated with health status, for instance, the level of irisin is significantly lower in obesity, osteoporosis/fractures, muscle atrophy, Alzheimer's disease, and cardiovascular diseases (CVDs), while higher in cancer patients. Irisin can bind to its receptor integrin-αV/β5 to induce browning of white fat, maintain glucose stability, keep bone homeostasis, and alleviate cardiac injury. But it is unclear whether it works by directly binding to its receptors to regulate muscle regeneration, promote neurogenesis, keep liver glucose homeostasis, and inhibit cancer development. Supplementation of recombinant irisin (r-irisin) or regular physical exercise activated irisin might be a successful strategy to fight obesity, osteoporosis, muscle atrophy, liver injury, and CVDs in one go. Here, we summarized the publications of FNDC5/irisin from PubMed/Medline, Scopus, and Web of science until March 2022, and review the role of FNDC5/irisin in physiology and pathology.